Chinese Legacy BC - Province of British Columbia - Ministry of International Trade (2017)
On May 15, 2014, the Government of British Columbia apologized to its Chinese Canadian community for historical wrongs. It also committed to provide a legacy for all British Columbians so that we can learn more about a time we cannot and should not forget. This website is a part of that legacy. It offers resources that document the history of the discrimination, chronicle the consultation process and formal Apology in the Legislature, and provide updates on the many legacy projects that highlight the substantial contributions Chinese Canadians have made to the culture, history and economic prosperity of our province. –Website description